Factors Affecting The Use of Contraceptives in Women of Childbearing Age in Wemeda Village - Lado, Bonavantura Lama; Ndoen, Honey Ivone; Sahdan, Mustakim (Timorese Journal of Public Health, 2021)
Contraceptive use is one of the variables that affect fertility. In using contraceptives, women need to consider several factors including the degree of health status, the emergence of side effects of failure or pregnancy that is not expected by each partner's consent, environmental and family cultural values. as many as 98 people but in 2020 experienced a decrease of 64 people. The purpose of this study was to analyze the factors that influence the use of contraception in women aged fertile soil in Wemeda village, East Malacca district, Malacca district. This type of research is an analytic survey with a cross sectional research design. The population in this study was 310 WUS and the sample was 74 WUS using simple random sampling technique. The research location was in Wemeda village, East Malaka District, Malacca district in April - December 2020. The results showed that the factors related to the use of contraceptives were: age (p-value = 0.005), level of knowledge (p-value = 0.009). family income (p-value = 0.023), husband's support (p-value = 0.015), and number of children (p-value 0.021), while factors that do not have a relationship with the use of contraceptives include education (p-value = 0.774). , support for health workers (p-value= 0.493), and distance to health facilities (p-value= 0.347).